2021
DOI: 10.1002/cbin.11586
|View full text |Cite
|
Sign up to set email alerts
|

ZNF667 attenuates leukocyte‐endothelial adhesion via downregulation of P‐selectin in skin flap following remote limb ischemic preconditioning

Abstract: We assessed the effects and potential mechanism of romote ischemic preconditioning (RIPC) on leukocytes‐endothelium cell adhesion in the flap microvessel after ischemia‐reperfusion (I/R) injury. Eight hours after reperfusion, edema and intravascular leukocyte aggregation were reduced and microvessels were more obvious in the group with superficial inferior epigastric artery (SIEA) perforator flap (SIEA‐flap) subjected to RIPC than in the I/R group. Zinc finger protein 667 (ZNF667) was significantly increased b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In a study on laryngeal squamous cell carcinoma (LSCC), it was found that ZNF667 is a tumor-suppressing gene [64][65][66][67][68]. ZNF667 can regulate P-selectin expression in specific cells and leukocyte-endothelial adhesion after hypoxia [69].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on laryngeal squamous cell carcinoma (LSCC), it was found that ZNF667 is a tumor-suppressing gene [64][65][66][67][68]. ZNF667 can regulate P-selectin expression in specific cells and leukocyte-endothelial adhesion after hypoxia [69].…”
Section: Discussionmentioning
confidence: 99%